2010
DOI: 10.1111/j.1600-0714.2010.00973.x
|View full text |Cite
|
Sign up to set email alerts
|

5-aminolevulinic acid induce apoptosis via NF-κB/JNK pathway in human oral cancer Ca9-22 cells

Abstract: These results demonstrate significant involvement of caspase-8 and -9 and their upstream NF-κB-JNK pathways in ALA-PDT-induced apoptosis. Future studies on how NF-κB and JNK activity regulate ALA-PDT response should provide a better strategy for the treatment of oral cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 32 publications
(50 reference statements)
1
24
0
1
Order By: Relevance
“…5-ALA induces effective accumulation of PS Pp IX in tumor cell and has high clearance rate in vivo without phototoxicities. Some studies have demonstrated that 5-ALA/PDT can effectively inhibit the growth of cancer cells in vitro (Peng et al, 1997;He et al, 2008;Chen et al, 2011a;Chen et al, 2011b;Gui et al, 2012). The same PDT result in our study also demonstrated that 5-ALA/PDT induced cytotoxicity depending on PS concentrations.…”
Section: Discussionsupporting
confidence: 78%
“…5-ALA induces effective accumulation of PS Pp IX in tumor cell and has high clearance rate in vivo without phototoxicities. Some studies have demonstrated that 5-ALA/PDT can effectively inhibit the growth of cancer cells in vitro (Peng et al, 1997;He et al, 2008;Chen et al, 2011a;Chen et al, 2011b;Gui et al, 2012). The same PDT result in our study also demonstrated that 5-ALA/PDT induced cytotoxicity depending on PS concentrations.…”
Section: Discussionsupporting
confidence: 78%
“…The activation of NF-κB induced by PDT was first found by Ryter et al in their study on the Photofrinmediated PDT treatment of leukemia in 1993 [21]. Researchers have subsequently found this phenomenon in PDT mediated by other photosensitizers, such as 5-ALA and zinc phthalocyanine [22][23][24]. Activated NF-κB induced cell apoptosis through the JNK pathway in a study of Ca9-22 oral cancer cells treated with 5-ALA-PDT [22].…”
Section: Discussionmentioning
confidence: 90%
“…Researchers have subsequently found this phenomenon in PDT mediated by other photosensitizers, such as 5-ALA and zinc phthalocyanine [22][23][24]. Activated NF-κB induced cell apoptosis through the JNK pathway in a study of Ca9-22 oral cancer cells treated with 5-ALA-PDT [22]. Broekgaarden et al found that siRNA knockdown of NF-κB increased survival signaling in murine breast carcinoma (EMT-6) cells and exacerbated the inflammatory response in murine RAW 264.7 macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies examined the role of JNK in mediating the apoptotic effect of several pharmacological agents or anticancer drugs in HNSCC cell lines, including N-(4-hydroxyphenyl) retinamide (4HPR), pepsin-digested bovine lactoferrin, 5-aminolevulinic acid, MLN4924, 6-(N, N -dimethylamino)-2-(naphthalene-1-yl) -4-quinazolinone, fomitoside-K, mevastatin and AZD8055 (an mTOR inhibitor), and their biological mechanisms of apoptosis (48)(49)(50)(51)(52)(53)(54)(55). Consistent with the present results, an antitumor role of JNK has been proposed upon treatment of HNSCC cells with the JNK inhibitor SP600125, which diminished the aforementioned pharmacological agents-induced apoptosis (47)(48)(49)(50)(51)(52)(53)(54). Similarly, Li and Johnson (56) demonstrated that pharmacological inhibition of JNK with SP600125 markedly inhibited bortezomib-induction of autophagy regulatory proteins and autophagosome formation in HNSCC.…”
Section: Discussionmentioning
confidence: 99%